(Not) thinking about the future: Inattention and maternal labor supply - Ana Costa-Ramón; Ursina Schaede; Michaela Slotwinski; Anne Ardila Brenøe (University of Zurich, Department of Economics, 2024)
The "child penalty" significantly reduces women's lifetime earnings and pension savings, but it remains unclear whether these gaps are the deliberate result of forward-looking decisions. This paper provides novel evidence on the role of information constraints in mothers' labor supply decisions. We first document descriptively that mothers are largely inattentive to the long-term financial consequences of reduced hours. In a large-scale field experiment that combines rich survey and administrative data, we then provide mothers with objective, individualized information about the long-run costs of reduced labor supply. The treatment increases demand for financial information and future labor supply plans, in particular among women who underestimate the long-term costs. Leveraging linked employer administrative data one year post-intervention, we observe that mothers who underestimate the long-term costs increase their labor supply by 6 percent over the mean.
Keywords: J16; J22; 330